The CAD Digital Automation Analysis of Costume Designing Based on Immersive Virtual Reality Models. (16th April 2022) - Zheng, Pan
Abstract : With the development of the social economy, costume design is becoming more and more trendy and diversified, which can better reflect cultural and geographical elements. However, traditional costume design often causes excessive waste of resources and time, which is an issue worthy of attention and value. In view of these limitations, an immersive virtual reality model is introduced in this paper. Digitization is realized based on CAD through combing the business logic involved in the costume design process, and virtual fitting and virtual sewing are realized according to virtual reality, and the effect of virtual dressing is viewed and adjusted according to the corresponding feedback, saving cost and time. The simulation experiment research shows that the immersive virtual reality model is effective and can effectively achieve the effective improvement of intrinsic motivation and self-efficacy. Meanwhile, it has a good effect in the assessment of costume design learning transfer and can effectively support the analysis of CAD digital automation.